Testing the effectiveness of different wash protocols to remove body surface contaminants in invertebrate food web studies - Melissa Jüds; Kerstin Heidemann; Bernhard Eitzinger; Stefan Scheu (PeerJ, 2023)
Molecular gut content analysis via diagnostic PCR or high-throughput sequencing (metabarcoding) of consumers allows unravelling of feeding interactions in a wide range of animals. This is of particular advantage for analyzing the diet of small invertebrates living in opaque habitats such as the soil. Due to their small body size, which complicates dissection, microarthropods are subjected to whole-body DNA extraction-step before their gut content is screened for DNA of their food. This poses the problem that body surface contaminants, such as fungal spores may be incorrectly identified as ingested food particles for fungivorous species. We investigated the effectiveness of ten methods for body surface decontamination in litter-dwelling oribatid mites using Steganacarus magnus as model species. Furthermore, we tested for potential adverse effects of the decontamination techniques on the molecular detection of ingested prey organisms. Prior to decontamination, oribatid mites were fed with an oversupply of nematodes (Plectus sp.) and postmortem contaminated with fungal spores (Chaetomium globosum). We used diagnostic PCR with primers specific for C. globosum and Plectus sp. to detect contaminants and prey, respectively. The results suggest that chlorine bleach (sodium hypochloride, NaClO, 5%) is most efficient in removing fungal surface contamination without significantly affecting the detection of prey DNA in the gut. Based on these results, we provide a standard protocol for efficient body surface decontamination allowing to trace the prey spectrum of microarthropods using molecular gut content analysis.